Implementation of competency approach in teaching mathematics to primary school children - Tatiana V. Mayasova, Oksana V. Kolesova, Nadezda N. Demeneva, Elena G. Gutsu, Elena V. Kochetova (Opción, 2019)
The article considers implementing the competency approach in teaching mathematics at primary school. The research objective was to check the 4th and 5th grade schoolchildren’s skills in solving competency-oriented tasks. The authors used the diagnostic technique consisting in solving mathematical problems that require application of knowledge to real-life situations, understanding of real-life quantities and geometrical figures, and ability to behave relevantly in real-life situations. Typical errors were identified and recommendations on their correction were given. The effective implementation of competency approach requires improving the methods of teaching mathematics at primary school.